Nadine : a social robot that can localize objects and grasp them in a human way - Thalmann, Nadia Magnenat (2020)
What makes a social humanoid robot behave like a human? It needs to understand and show emotions, has a chat box, a memory and also a decision-making process. However, more than that, it needs to recognize objects and be able to grasp them in a human way. To become an intimate companion, social robots need to behave the same way as real humans in all areas and understand real situations in order they can react properly. In this chapter, we describe our ongoing research on social robotics. It includes the making of articulated hands of Nadine Robot, the recognition of objects and their signification, as well as how to grasp them in a human way. State of the art is presented as well as some early results.